Commercial Organic Versus Conventional Whole Rye and Wheat Flours for Making Sourdough Bread: Safety, Nutritional, and Sensory Implications - Pontonio, Erica; Arora, Kashika; Dingeo, Cinzia; Carafa, Ilaria; Celano, Giuseppe; Scarpino, Valentina; Genot, Bernard; Gobbetti, Marco; Di Cagno, Raffaella (Frontiers in Microbiology, 2021)
Organic farming is gaining a broad recognition as sustainable system and consumer demand for organic products has increased dramatically in the recent past. Whether organic agriculture delivers overall advantages over conventional agriculture is however contentious. Here, the safety, nutritional and sensory implications of using commercial organic rye, soft and durum wheat flours rather than conventional to make sourdough bread have been investigated. Culture-dependent and -independent approaches were used to explore the microbial architecture of flours and study their dynamics during sourdough propagation. Besides biochemical features, the main nutritional (amino acids content, asparagine level, antioxidant activity) characteristics of sourdoughs were investigated and their effect on the structural, nutritional and sensory profile of breads assessed. Overall, the organic farming system led to flours characterized by lower content of asparagine, and cell density of Enterobacteriaceae while showing higher concentration of total free amino acids. Differences of the flours mirrored those of sourdoughs and breads. The use of sourdough fermentation guaranteed a further improvement of the flour characteristics, however a microbial and sensory profile simplification as well as a slight decrease of the biochemical parameters were observed between breads with sourdough after one-cycle fermentation and ten days of propagation.